TOURISM DEVELOPMENT ANALYSIS TAMIANG BAY MARINE KOTABARU REGENCY SOUTH KALIMANTAN - Muchtar, Muchtar; Dwujayani, Henny; Jatmiko, Anang Rohmad; Widodo, Moch. Heru (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
This study aims to analyze the potential and constraints of developing marine ecotourism in Tamiang, Kotabaru Regency, South Kalimantan. The research was conducted using an interpretive qualitative approach. The data analysis was carried out simultaneously with the data collection process. The research focuses on the potential and constraints of the marine ecotourism. The results found the potential for the marine ecotourism that is beautiful natural conditions, clean, shallow beaches with clear water and not big waves. Other potentials are found in local cultural attractions, opportunities for local economic growth along with the development of ecotourism, friendly people and open to the presence of tourists. In addition, there are also many coral reefs and a land in the middle of the bay that has not been managed. The obstacle to the marine ecotourism are; the damaged road, no accommodation facilities like restaurants and hotel, minimal transportation facilities like boats to surround the bay, no intensive promotional activities, limited facilities for snorkeling and boarding, and also not yet developed institutions. The formulation of the Tamiang Bay marine ecotourism strategy is based on the vision, mission, goals, objectives of Kotabaru Regency in the tourism sector and is determined through internal and external environmental analysis, identification of potentials and constraints.